Psychological testing in everyday life history, science, and practice - Goldfinger, Karen (SAGE Publications, Inc., 2019)
Psychological Testing in Everyday Life explores how psychological testing is used in real-life setting to make the study of psychometrics interesting, relevant, and highly accissible. Author Karen B. Goldfinger examines a broad range of carefully selected topics to capture student interest, encourage critical thinking, and spark class discussions. This unique text will support students in becoming thoughtful, informed consumers and providers of psychological assessment.